Comparison of computed tomography, endosonography, and intraoperative assessment in TN staging of gastric carcinoma. Issue 5 (May 1993) - Ziegler, K; Sanft, C; Zimmer, T; Zeitz, M; Felsenberg, D; Stein, H; Germer, C; Deutschmann, C; Riecken, E O
Abstract : From 1986 to 1990 a prospective comparative study was undertaken to compare the relative accuracy of computed tomography, endogastric ultrasonography, and intraoperative surgical assessment in evaluating the depth of invasion (T category) and involvement of lymph nodes (N category) of patients with gastric carcinoma. One hundred and eight consecutive patients, who were treated by total gastrectomy and previously evaluated with computed tomography, endogastric ultrasonography, and intraoperative surgical assessment, entered the study. Results (T and N category) were compared with those of histopathological staging (pT and pN category). T categories were correctly staged in 43% of cases with computed tomography, 86% with endogastric ultrasonography, and 56% with intraoperative surgical assessment. Computed tomography scanning correctly staged 51% of all N1 and N2 lymph nodes compared with 74% for endogastric ultrasonography and 54% for intraoperative surgical assessment. In general, computed tomography was more accurate for advanced stages of cancer and showed a tendency to overstage the T category and understage N category of gastric tumours. By contrast, endogastric ultrasonography was equally accurate for all T categories and showed an understaging for N categories. Intraoperative surgical assessment overstaged early T stages, understaged T4 tumours, and was equally accurate for all grades of N categories. Computed tomography scanning and intraoperative surgical assessment of T and N categories were of little value in staging of gastric carcinoma. Endogastric ultrasonography is more accurate than computed tomography scanning and intraoperative surgical assessment. Therefore endogastric ultrasonography should be introduced in the preoperative assessment of patients with gastric carcinoma.